En bloc : a collection of stories - Tan, Eugenia Yanxin (2015)
En Bloc is a collection of short fictional horror stories, set in a single block of HDB flats in the heartlands of Singapore. They are a reflection of heartland life, but at the same time, they also highlight how living in a HDB flat can be a socially and physically isolating experience. There are certain kinds of horrors that can be found in this isolation, which enables it to ripen and manifest. Other than wanting to write stories that both entertain and terrify the reader, it is also important that my stories mirror life in the heartlands, as a reflection of Singaporean society and what potential horrors can lurk beneath, hidden from the average local’s eyes. In this exegesis, I will discuss the readings that informed my approach to writing, as well as share what I have learned about writing in the process of working on this collection.